High risk areas of snatch theft in Kuala Lumpur, Putrajaya, and Selangor, Malaysia - Norita Jubit,; Tarmiji Masron,; Mohd Sofian Redzuan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Kuala Lumpur and Selangor are among 14 states in Malaysia that are listed in the high number of reported cases of snatch theft. Basically, public lack of vigilance towards their belongings creates opportunities for criminals to commit crime. On the other hand, criminals are constantly seeking for the opportunity to target their victims when there is an opportunity to do so. This study employs the Getis Ord Gi* method and aims to identify areas of high risk in snatch theft cases with statistical significance by effectively measuring the probability of the null hypothesis. This study uses 111 station boundaries as units of analysis. The attribute data consists of reported snatch theft cases between 2015-2020. It includes cases reported by police station, the frequency of crime and gender of the complainants. The result of the study revealed that the hot spots areas with highest z score >2.58 over 5 years are in Tun H.S. Lee and Dang Wangi whereby these two areas are the main pedestrian entry to shopping complexes. Both areas are detected as repeated hot spots of snatch theft for the period of 2015-2020. The novelty of this study lies in its discovery of statistically significant snatch theft hotspots within the police station boundaries in Federal Territory of Kuala Lumpur and Selangor. Previous studies tend to identify hotspots that employs choropleth map and utilized district and city boundaries as unit of analysis for identifying these hotspots.